2018
DOI: 10.24252/kesehatan.v11i2.5415
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Dukungan Keluarga Dengan Efikasi Diri Penderita Tuberculosis Multidrug Resistant (Tb-Mdr) Di Poli Tb-MDR Rsud Ibnu Sina Gresik

Abstract: TB-MDR terjadi karena kegagalan pengobatan, putus pengobatan, atau pengobatan yang tidak benar sehingga terjadinya resistensi primer. Penelitian ini bertujuan untuk menganalisis hubungan antara dukungan keluarga dengan Efikasi Diri penderita Tuberkulosis resisten obat di Poli TB-MDR RSUD Ibnu Sina Gresik. Metode : Desain penelitian deskriptif korelasional melibatkan 15 responden Penderita TB-MDR yang sedang menjalani pengobatan di poli TB-MDR RSUD Ibnu Sina Gresik pada 28 Maret-28 Juni 2018 yang di pilih mengg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
3
0
4
Order By: Relevance
“…The study's result found that the least cause of the incidence of MDR-TB at Ibnu Sina Hospital Gresik was the presence of high family support, with only a small amount of low family support. The family is the closest and most understanding person to the sufferer to provide full support for MDR-TB sufferers because the patient consumes the drug for a long time (Hasanah, Makhfudli, and Wahyudi 2018). Based on the results of interviews and observations, it was found that family support was high in the MDR-TB poly because kinship in Javanese culture has harmonious behavior between neighbors and family, shy attitude, feeling uncomfortable because they are worried about offending feelings (Ulya and Nugroho 2020).…”
Section: Family Supportmentioning
confidence: 99%
“…The study's result found that the least cause of the incidence of MDR-TB at Ibnu Sina Hospital Gresik was the presence of high family support, with only a small amount of low family support. The family is the closest and most understanding person to the sufferer to provide full support for MDR-TB sufferers because the patient consumes the drug for a long time (Hasanah, Makhfudli, and Wahyudi 2018). Based on the results of interviews and observations, it was found that family support was high in the MDR-TB poly because kinship in Javanese culture has harmonious behavior between neighbors and family, shy attitude, feeling uncomfortable because they are worried about offending feelings (Ulya and Nugroho 2020).…”
Section: Family Supportmentioning
confidence: 99%
“…Pernyataan diatas didukung oleh hasil penelitian Hasanah et al (2018) yang bertolak belakang dengan penelitian ini dimana hasil analisis menunjukkan dukungan keluarga tidak berhubungan secara signifikan terhadap efikasi diri. Disebutskan bahwa faktor dalam membentuk efikasi diri bukan hanya dari dukungan keluarga, melainkan pendidikan, pengetahuan, sikap, tingginya harga diri, dan kemampuan yang cukup untuk mengambil tindakan dalam mengubah situasi.…”
Section: Pembahasanunclassified
“…Dukungan keluarga sangat diperlukan dalam proses pemulihan, sehingga walaupun pasien telah berpengetahuan baik tentang penyakitnya tetapi jika dukungan keluarga kurang maka pasien akan menjadi kurang patuh dalam menjalani pengobatan (23). Individu yang memperoleh dukungan keluarga tinggi akan menjadi lebih optimis dalam menghadapi masalah kesehatan serta kehidupannya akan lebih terampil dalam memenuhi kebutuhan psikologi (24).…”
Section: Strategi Dots DI Ruang Pipit Rsu Anutapura Paluunclassified